Intracerebroventricular injection of Wharton’s jelly mesenchymal stem cells attenuates Brain Damage in Rat Model of Hypoxia: Optimization of vascular endothelial growth factor and downregulation of inflammatory factors - Mehrannia, Kobra; Mokhtari, Tahmineh; Noori Mogehi, Seyed Mohammad Hossein; Akbari, Mohammad; Tavakkoly Bazzaz, Javad; Mahakizeh, Simin; Mohammai, Yousef; Ijaz, Sahar; Hassanzadeh, Gholamreza (Journal of Contemporary Medical Sciences, 2018)
Objective: In this study, we investigated the effects of intracerebroventricular (ICV) Wharton’s jelly mesenchymal stem cells (WJ-MSCs) injection in rat model of hypoxic brain injury by evaluating the amount of vascular endothelial growth factor (VEGF) and pro inflammatory factors in hippocampus. Methods: 24 rats were allocated to four groups of study:1) control and intact animals (Co), 2) sham group (Sh): animals were placed in the hypoxia chamber without inducing hypoxia and injected PBS, 3) hypoxia (H), 4) H+WJ-MSC, Hypoxia was induced by placing animals in the hypoxia chamber for 30 days (4hours a day). After three days of vehicle or WJ-MSCs injection, the rats were sacrificed and brain tissues were prepared for molecular and histopathological studies. Results: Despite a decrease in the gene expression of IL1β, TNFα, IL18, and the number of dark neurons in CA1 region of hippocampus in H+ WJ-MSC groups Compared to H (P˂0.05). There is an increase in all these factors in both H and H+WJ-MSC groups compared to CO and Sh groups (P˂0.05). The gene expression and protein concentration of VEGF increased in both H and H+WJ-MSC groups compared to Co and Sh groups (P˂0.05). Conclusion: Based on the findings, WJ-MSCs could reduce the number of dark neurons in hippocampus by increasing the VEGF synthesis and reducing inflammation in hypoxic condition.